2021
DOI: 10.3390/ani11071860
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Dynamics as an Alternative Method for Detection of Bimodal Milk Ejection in Dairy Cows

Abstract: The primary objective of our study was to assess the ability of a vacuum recorder to detect the presence of bimodal milk flow curves in dairy cows compared with a portable milk flow meter. In a cross-sectional study, 241 individual cow milking observations were analyzed. We simultaneously collected (1) individual cow vacuum events during milking using portable vacuum recorders, and (2) individual cow milk flow curves by attaching a portable milk flow meter to the same milking unit. Presence of bimodality was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Evidence also suggests that, under certain circumstances, delayed milk ejection can cause reduced milk yield. The underlying concept has been recently described by Erskine et al (2019) and seconded by work from our group (Wieland et al, 2021). However, the reader should keep in mind that a cause-effect relationship cannot be inferred from this observational study.…”
Section: Risk Factors For Chronically Delayed Milk Ejectionmentioning
confidence: 79%
“…Evidence also suggests that, under certain circumstances, delayed milk ejection can cause reduced milk yield. The underlying concept has been recently described by Erskine et al (2019) and seconded by work from our group (Wieland et al, 2021). However, the reader should keep in mind that a cause-effect relationship cannot be inferred from this observational study.…”
Section: Risk Factors For Chronically Delayed Milk Ejectionmentioning
confidence: 79%
“…Data for trial 2 were collected during 15 visits (Teaching Dairy Barn, 11 visits during the 11:00 a.m. milking session; commercial dairy, 4 visits during the 9:00 a.m. milking session). Individual cow vacuum events were collected during milking using VaDia (BioControl, Rakkestad, Norway) vacuum recorders as previously described [ 11 ]. For this purpose, 4 VaDia devices were installed at the first 2 stalls on each parlor side at the Teaching Dairy Barn, and 10 VaDia devices were installed at 10 consecutive stalls at the commercial dairy farm.…”
Section: Methodsmentioning
confidence: 99%
“…They found that cows with DME yielded 1.8–3.1 kg less milk per milking session than cows without DME [ 11 ]. In a study conducted at five dairy farms with a thrice-daily milking schedule in New York, USA [ 12 ], our group analyzed data from 241 cow milking observations and revealed that cows with a bimodal milk flow curve produced 1.3 kg less milk per milking session than those with a unimodal milk flow curve. Bruckmaier and Blum used 12 cows to study the effect of premilking stimulation on milk ejection and milk flow [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have shown that DME can have a negative impact on milking performance in dairy cows, this evidence is limited. For instance, the assessment of the association between DME and milking performance in previous studies was based on a single milking observation [ 4 , 11 , 12 ]. However, some cows may exhibit DME in every milking session, i.e., chronic DME [ 13 ], and the effect size of the association of DME with milking performance could differ according to the frequency of DME events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation